The effect of temperature on the vibration behaviour of laminated composite plates - Salhi, Mohamed Lamine; Mellas, Mekki; Ounis, Houdayfa (Zielona Góra: Uniwersytet Zielonogórski)
The present work is a contribution to the study of the effects of temperature on vibrations and stability of laminated composite plates using the finite element method. Thus, a DMQP/ml bending finite element with 4 nodes and 3 degrees of freedom based on the first order shear theory is extended to consider the effects of temperature on vibration and stability of laminated composite plates.
Keywords: laminated composite plates; thermal buckling; vibrations; finite-element method